Green Practices In Green Obligation: Risk’s Impact on Satisfaction, Loyalty, Word of Mouth, and Willingness to Pay - Ikbar Raniadi Fardan; Avanti Fontana (Green Publisher Indonesia, 2025)
Research Aims: This study aims to analyze the impact of green practices implemented by green bond issuers on customer satisfaction, loyalty, word of mouth, and willingness to pay, moderated by risk. Additionally, this study explores the moderating role of risk in the relationship between satisfaction, loyalty, and word of mouth towards willingness to pay.Design/methodology/approach: A quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) will be employed to analyze data from 320 existing investors and potential investors that haven’t invested in green bonds in Jabodetabek. Research Findings: The result revealed that green practices significantly impacts satisfaction, loyalty, word of mouth and willingness to pay. Also, satisfaction, loyalty, and word of mouth directly has positive impact on willingness to pay. And, customer satisfaction also impact positively on loyalty. Risk that hypothesized to be negatively impact satisfaction, loyalty and word of mouth relation to willingness to pay, didn’t have negative impact on each relationship Theoretical Contribution/Originality: This study contributes to the literature by extending the understanding of green financial behavior, particularly in the context of green bonds. It integrates green practices as a driver of customer satisfaction, loyalty, word of mouth, and willingness to pay, and examines risk as a moderating factor—an area that has received limited attention in sustainable investment research. The study provides empirical evidence using a structural equation modeling approach in the context of retail investors in an emerging market, thereby enriching the theoretical discussion on sustainable consumer behavior and green investment adoption.